Communicative Antecedents of Political Persuasion: Political Discussion, Citizen News Creation, and the Moderating Role of Strength of Partisanship. Issue 2 (4th March 2017) - Ardèvol-Abreu, Alberto; Barnidge, Matthew; de Zúñiga, Homero Gil
Abstract : Although much attention has been paid to how media use and interpersonal discussion motivate people to engage in political persuasion, and despite recent efforts to study the role of digital media technologies, less is known about the creation of news and public affairs content online. This study sheds light on how online content creation works alongside other communicative behaviors, such as news use and political discussion, to affect attempted political persuasion. Using two-wave panel survey data, we find that political discussion and citizen news creation mediate the relationships between online and traditional news use, on one hand, and attempted persuasion, on the other. Furthermore, strength of partisanship moderates the relationship between content creation and attempted persuasion. Findings are discussed in light of their implications for the political communication and public sphere processes.